Prevention and management of minor complications in percutaneous endoscopic gastrostomy - Kurt Boeykens; Ivo Duysburgh; Wim Verlinden (BMJ Open Gastroenterology)
Background Percutaneous endoscopic gastrostomy (PEG) was developed by Ponsky-Gauderer in the early 1980s. These tubes are placed through the abdominal wall mainly to administer fluids, drugs and/or enteral nutrition but can also be used for drainage or decompression. The tubes consist of an internal and external retention device. It is a generally safe technique but major or minor complications may arise during and after tube placement.Method A narrative review of the literature investigating minor complications after PEG placement.Results This review was written from a clinical viewpoint focusing on prevention and management of minor complications and documented with real cases from more than 21 years of clinical practice.Conclusions Depending on the literature the incidence of minor complications after gastrostomy placement can be high. To decrease associated morbidity, prevention, early recognition and popper management of these complications are important.